Functional Characterization of the SHIP1-Domains Regarding Their Contribution to Inositol 5-Phosphatase Activity - Spike Murphy Müller; Nina Nelson; Manfred Jücker (Biomolecules)
The Src homology 2 domain-containing inositol 5-phosphatase 1 (SHIP1) is a multidomain protein consisting of two protein–protein interaction domains, the Src homology 2 (SH2) domain, and the proline-rich region (PRR), as well as three phosphoinositide-binding domains, the pleckstrin homology-like (PHL) domain, the 5-phosphatase (5PPase) domain, and the C2 domain. SHIP1 is commonly known for its involvement in the regulation of the PI3K/AKT signaling pathway by dephosphorylation of phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P3) at the D5 position of the inositol ring. However, the functional role of each domain of SHIP1 for the regulation of its enzymatic activity is not well understood. To determine the contribution of the individual domains to catalytic activity, the full-length protein was compared with truncated constructs lacking one or more domain(s), regarding the substrate turnover (kcat) and catalytic efficiency (kcat/Km) towards ci8-PtdIns(3,4,5)P3. With this approach, it was possible to verify the allosteric activation of SHIP1 mediated by the C2 domain as described previously, while the PHL domain seemed instead to have a negative effect regarding catalytic efficiency. The full-length SHIP1 clearly displayed the highest turnover and the second-highest catalytic efficiency, showing the role of the SH2 domain and PRR not only in protein–protein interactions but also in catalysis. The SH2 domain increased substrate turnover but negatively affected catalytic efficiency. The linker between the SH2 and the PHL domains decreased the turnover number but positively influenced the catalytic efficiency. The PRR increased both the substrate turnover and the protein’s catalytic efficiency. The regression analysis of the Michaelis–Menten graph revealed SHIP1 to be an allosteric enzyme, with the PRR and the linker being the most involved domains in that regard. In summary, our data indicate a complex regulation of the enzymatic activity of SHIP1 by its individual domains. While the C2 domain and PRR at the carboxy-terminus have a positive effect on enzymatic activity, the SH2 and PHL domain at the amino-terminus inhibit catalytic efficiency.